1994
DOI: 10.1111/j.1365-2044.1994.tb03318.x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia after laparoscopic sterilization Effect of 2% lignocaine gel applied to Filshie clips

Abstract: SummaryWe performed a randomised controlled study in patients undergoing day case laparoscopic sterilisation to assess whether coating Filshie clips with 2% lignocaine gel prior to application to the Fallopian tubes would reduce postoperative pain. Sixty-two patients were studied, in 33 of whom the Filshie clips were coated in sterile 2% lignocaine gel. Pain scores in the Iignocaine gel group were significantly lower than in the control group at 1 h after return to the ward, but no diferences were found immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Our data support these studies and confirmed the limited duration of the local anesthetic effect with decreased narcotic use and pain scores on the day of surgery and the first postoperative day but no differences on the second postoperative day. Most previous studies included only minor gynecologic procedures such as tubal ligations, adhesiolysis, and adnexal procedures [19][20][21][22][23][24][25][26]. The results of our study as well as a study by Cruz et al [16] demonstrated that the superior pain control achieved with intraperitoneal administration of local anesthetic extends to patients undergoing minimally invasive hysterectomies and cancer staging procedures.…”
Section: Discussionsupporting
confidence: 63%
“…Our data support these studies and confirmed the limited duration of the local anesthetic effect with decreased narcotic use and pain scores on the day of surgery and the first postoperative day but no differences on the second postoperative day. Most previous studies included only minor gynecologic procedures such as tubal ligations, adhesiolysis, and adnexal procedures [19][20][21][22][23][24][25][26]. The results of our study as well as a study by Cruz et al [16] demonstrated that the superior pain control achieved with intraperitoneal administration of local anesthetic extends to patients undergoing minimally invasive hysterectomies and cancer staging procedures.…”
Section: Discussionsupporting
confidence: 63%
“…Pain after laparoscopic cholecystectomy may be ascribed to the surgical incision, carbon dioxide insufflation and visceral pain. Techniques which are of value in reducing postoperative pain following laparoscopy include rectus sheath block ( 5, 6), the use of an abdominal drain for a few hours postoperatively to allow the escape of carbon dioxide ( 7), and topical application of local anaesthetic to the viscera ( 8) or to laparoscopic clips ( 9). We have shown that splashing a single diluted dose of lidocaine with saline under the surface of the right diaphragmatic area following the laparoscopic procedure significantly reduced the intensity of postoperative shoulder and abdominal pain immediately on return to the ward and the following 24 h postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations from international bodies suggest that a 10% to 20% reduction should be expected in chronic pain trials, and this is likely to be the case in acute pain also [47,48]. A previous systematic review in the field of gynecologic laparoscopy exists [49]; however, this is now out of date, limited to intraperitoneal administration, includes unpublished research [50], includes medical devices coated with anesthetic [51,52], and includes anesthetic agents combined with other medications [53,54], reducing its applicability. A further meta-analysis of trials using local anesthetic during laparoscopic cholecystectomy demonstrated reduction in postsurgical pain in the immediate (0−6 hours) postoperative period [55].…”
Section: Discussionmentioning
confidence: 99%